Varenicline for Smoking Cessation: a Review - Rauniar, G P; Mishra, A; Sarraf, D P (Health Renaissance, 2016)
Tobacco use is the leading cause of preventable death and disability in the world. Although gradually declining in most developed countries, the prevalence of tobacco use has increased among developing countries. Nicotine is an addictive chemical that is inhaled from the tobacco present in the cigarettes. It acts on neuronal nicotinic acetylcholine receptors within the ventral tegmental area of the brain, causing dopamine release in the nucleus accumbens which reinforces nicotine-seeking behavior. Reward through the dopaminergic system is a common thread among many drugs of addiction. According to the National Anti-Tobacco Communication Campaign Strategy for Nepal smoking prevalence in Nepal is higher (38.4%) than the smoking prevalence in the world (29%). Smoking attributable annual deaths in Nepal is estimated at nearly 14,000 (9,000 male deaths and 5,000 female deaths) for population aged 35 and over. First-line pharmacotherapies for smoking cessation are varenicline, sustained-release bupropion and various forms of nicotine replacement therapy (i.e., patch, gum, lozenge, inhaler, nasal spray). These drugs can be used as monotherapy or combination therapy for the treatment of smoking cessation. After studying the outcome of many clinical trials and meta-analysis, it is concluded that cigarette smokers taking varenicline have the most success quitting smoking as compared with those taking other first-line pharmacotherapies for treating smoking cessation. Health Renaissance 2014;12(3): 215-220